2008
DOI: 10.1016/j.jallcom.2007.10.116
|View full text |Cite
|
Sign up to set email alerts
|

The isothermal section of the phase diagram of the Dy–Er–Co ternary system at 773K

Abstract: The isothermal section of the phase diagram of the Dy-Er-Co ternary system at 773 K was investigated by X-ray powder diffraction (XRD), differential thermal analysis (DTA) and optical microscopy. The result shows that this section consists of 9 single-phase regions and 8 two-phase regions, and no three-phase region. The compounds Dy Co form a continuous series of solid solutions. In addition, the single phases Dy and Er also form a continuous series of solid solution. The binary compounds DyCo 5 and ErCo 5 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
3
4
0
Order By: Relevance
“…[27,28] that the existence of compound Dy 4 Co 3 was not observed in the vicinity of 773 K. Later, Ref. [29] confirmed that the existence of compound Dy 4 Co 3 was observed at 773 K. The existence of compound Dy 4 Co 3 was observed at 773 K in this work. The X-ray diffraction pattern of the sample with composition of Dy 57.14 Co 42.86 shown in Fig.…”
Section: Phase Analysissupporting
confidence: 71%
See 1 more Smart Citation
“…[27,28] that the existence of compound Dy 4 Co 3 was not observed in the vicinity of 773 K. Later, Ref. [29] confirmed that the existence of compound Dy 4 Co 3 was observed at 773 K. The existence of compound Dy 4 Co 3 was observed at 773 K in this work. The X-ray diffraction pattern of the sample with composition of Dy 57.14 Co 42.86 shown in Fig.…”
Section: Phase Analysissupporting
confidence: 71%
“…The result obtained in this work agrees with Refs. [25,26,29]. At 773 K the existence of seven binary compounds Ho 2 Co 17 , Ho 2 Co 7 , HoCo 3 , HoCo 2 , Ho 4 Co 3 , Ho 12 Co 7 and Ho 3 Co were confirmed in Ho-Co binary system in this work.…”
Section: Phase Analysissupporting
confidence: 67%
“…[13,14], the authors have studied the R 4 Co 3 (R = Gd, Tb, Dy) phase. The result shows the single phases R 4 Co 3 (R = Tb, Dy) are formed hardly even after annealed for a long time at low temperatures.…”
Section: Binary Systemmentioning
confidence: 99%
“…For further studying R x Co y alloys, the phase diagram of R 1 -R 2 -Co ternary systems is essential to have a detailed knowledge. Before this work, we have studied the Dy-Er-Co, Gd-Tb-Co, Gd-Dy-Co and Pr-Nd-Co phase diagram [13][14][15][16], and this work is continuation of systematic investigation of R 1 -R 2 -Co ternary systems. In this work, we studied the isothermal section of Tb-Dy-Co ternary system phase diagram at 773 K and experimentally determined the vertical section of pseudobinary system and magnetic property of Tb 1−x Dy x Co 2 (x from 0 to 1) series alloys.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that there are eight intermetallic compounds existing in the Co-Er system, i.e., Co 17 Er 2 , Co 5 Er, Co 7 Er 2 , Co 3 Er, Co 2 Er, Co 3 Er 4 , Co 7 Er 12 , and CoEr 3 [2]. Zhuang et al have also studied the compounds R 4 Co 3 (R = Er, Dy) and confirmed the existence of Er 4 Co 3 [3] after long time annealing for homogenization treatment. There are ten binary compounds reported in the Co-Nd system, i.e., Co 17 Nd 2 , Co 5 Nd, Co 19 Nd 5 , Co 7 Nd 2 , Co 3 Nd, Co 2 Nd, Co 3 Nd 2 , Co 1.7 Nd 2 , Co 3 Nd 7 , and CoNd 3 [1].…”
Section: Introductionmentioning
confidence: 99%